Cardiac vagal afferent neurotransmission in health and disease: review and knowledge gaps - van Weperen, Valerie Y. H.; Vaseghi, Marmar (Frontiers in Neuroscience, 2023)
The meticulous control of cardiac sympathetic and parasympathetic tone regulates all facets of cardiac function. This precise calibration of cardiac efferent innervation is dependent on sensory information that is relayed from the heart to the central nervous system. The vagus nerve, which contains vagal cardiac afferent fibers, carries sensory information to the brainstem. Vagal afferent signaling from the heart has been shown to increase cardiac parasympathetic efferent response and vagal tone. In the setting of heart failure and myocardial infarction, cardiac vagal afferent neurotransmission is altered, though much remains unknown. Even though the subsequent cardiac autonomic imbalance after cardiac injury is characterized by sympathoexcitation and parasympathetic dysfunction, it remains unclear if, and to what extent, vagal afferent dysfunction is involved in the development of vagal withdrawal. This review aims to summarize the current understanding of cardiac vagal afferent neurotransmission in health and in the setting of cardiovascular disease, especially after myocardial infarction, and to highlight the knowledge gaps that remain to be addressed.